2018
DOI: 10.20453/rmh.v29i2.3347
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans en heces de palomas (Columba livia) en Lima Metropolitana

Abstract: Objetivos: Investigar la presencia del hongo levaduriforme Cryptococcus neoformans en heces de palomas domésticas (Columba livia). Material y métodos: Estudio descriptivo transversal realizado en la ciudad de Lima-Perú. Se recolectaron 300 muestras de heces encontradas en los suelos de parques y hospitales. Además se tomó 30 muestras de las cloacas de algunas palomas capturadas. Resultados: Se aisló el hongo en 47 muestras de las que 7 correspondieron al Cryptococcus neoformans var. neoformans pero no se aisló… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
2
3
0
2
Order By: Relevance
“…Similar results were also found in the regions of Popayán, Cundinamarca, Bogotá, and Cali (Figure 4). Likewise, this species is strongly associated with avian droppings, generally from pigeons (C. livia) [87], which is consistent with the findings described Kwon-Chung and Bennett in 1984 [47], who established the primary environmental source of C. neoformans as being pigeon droppings, which was contrary to the findings reported by Cogliati et al, who that suggested that poultry feces is a secondary and transitory niche [53,93].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar results were also found in the regions of Popayán, Cundinamarca, Bogotá, and Cali (Figure 4). Likewise, this species is strongly associated with avian droppings, generally from pigeons (C. livia) [87], which is consistent with the findings described Kwon-Chung and Bennett in 1984 [47], who established the primary environmental source of C. neoformans as being pigeon droppings, which was contrary to the findings reported by Cogliati et al, who that suggested that poultry feces is a secondary and transitory niche [53,93].…”
Section: Discussionsupporting
confidence: 88%
“…According to the samples registered for the different studies, the presence of the C. neoformans complex is generally associated with debris from trees of the genus Eucalyptus and Ficus sp., as stated by Lazéra et al [ 96 ] and Cogliati et al, who found associations with arboreal specimens as niches and stable reservoirs [ 53 , 93 ]. Similar results were also found in the regions of Popayán, Cundinamarca, Bogotá, and Cali ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A infecção pode ser apenas pulmonar ou disseminada, causando uma micose sistêmica, podendo afetar até mesmo o sistema nervoso central (meningite fúngica). A criptococose é mais comum em pessoas imunocomprometidas, sendo, portanto, considerada uma doença oportunista (HUAMÁN et al, 2018).…”
Section: Criptococoseunclassified